Smart buildings: a new environment(theoretical approach) - Akram, Omar Khasro; Franco, Daniel Jose; Ismail, Sumarni (IJETMAS, 2016)
This research addresses the smart buildings and their inside and outside environment and technology types. The aim of this study is to understand the main actors responsible for such buildings and houses and environmental impact as well as their main characteristics, which we call "smart" features. Directly related to advanced technology, this paper aims also to describe their use and types, not just in a global way, but also in light technical approach, identifying components and elements present in a home automation system and how user interacts with it in a way that normal people, without technical knowledge can understand.